1998
DOI: 10.1016/s0014-5793(98)00064-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the human serum paraoxonase 55 and 192 genetic polymorphisms on the protection by high density lipoprotein against low density lipoprotein oxidative modification

Abstract: Human serum paraoxonase (PON1) associated with high density lipoprotein (HDL) has been postulated to have a role in protecting low density lipoprotein (LDL) against oxidative modification, which has led to the proposal that PON1 is an antiatherogenic, anti-inflammatory enzyme. PON1 has two genetically determined polymorphic sites giving rise to amino-acid substitutions at positions 55 (LC CM) and 192 (RC CQ) and therefore 4 potential alloenzymes. We have examined the effects of these molecular polymorphisms on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
218
3
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(247 citation statements)
references
References 25 publications
18
218
3
3
Order By: Relevance
“…This is of interest because PON1 192 polymorphism can greatly modify the ability of PON1 to protect lipids against oxidation. In vitro studies showed that RR homozygotes were less effi cient than QQ and QR individuals in protecting lowdensity lipoproteins from copper-induced oxidation ( 44 ). In addition, several case-control studies have reported disease, in which a decreased serum PON1 activity was found to be associated with increased PON1 protein expression ( 13,14 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is of interest because PON1 192 polymorphism can greatly modify the ability of PON1 to protect lipids against oxidation. In vitro studies showed that RR homozygotes were less effi cient than QQ and QR individuals in protecting lowdensity lipoproteins from copper-induced oxidation ( 44 ). In addition, several case-control studies have reported disease, in which a decreased serum PON1 activity was found to be associated with increased PON1 protein expression ( 13,14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be difficult to understand how higher levels of a protein that is known to have antioxidant properties can be associated with AMD. For a possible explanation, we would like to emphasize that variant p.L55M has been reported to affect PON1 activity towards lipid peroxides, with the LL genotype being less effective than MM at protecting LDL against oxidation (Mackness et al 1998a). Since alleles at position -107C and -162A are in linkage disequilibrium with variant 55L, they are likely to be also associated with the less effective protection against oxidation, thus can confer the risk for AMD and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are two annotated missense SNPs within the PON1 coding region: p.L55M (rs854560), where the major allele L leads to elevated PON1 protein levels, and p.Q192R (rs662), affecting substrate specificity as well as enzyme activity (Garin et al 1997;Humbert et al 1993). These two missense polymorphisms affect also the ability of HDL to protect LDL from oxidative modifications, with MM/QQ genotype being most effective (Mackness et al 1998a). The level of PON1 concentration in serum is also affected by sequence variants within the promoter of the PON1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…18 Therefore, the protecting role of PON is the subject of considerable debate. 19 -21 There are allelic variants in the human PON1 gene, a glutamine (Q allele) for arginine (R allele) at codon 192 and a methionine (M allele) to leucine (L allele) at codon 55, that have been studied and associated with susceptibility to Other studies have proved that the HDL isolated from QQ/MM homozygous subjects have lowest activity toward paraoxon 22,26 and greatest protective capacity toward LDL oxidation in vitro. 26 Therefore, CLA-1 receptor plays a central role in FC and HDL-CE uptake but a preferential selective uptake of CEOOHs regarding unoxidized CE as described.…”
mentioning
confidence: 99%
“…Arylesterase activity lies on the same protein, correlated with the 55 variant, and is considered an index of protein concentration. 22 Other studies have proved that the HDL isolated from QQ/MM homozygous subjects have lowest activity toward paraoxon 22,26 and greatest protective capacity toward LDL oxidation in vitro. 26 Therefore, CLA-1 receptor plays a central role in FC and HDL-CE uptake but a preferential selective uptake of CEOOHs regarding unoxidized CE as described.…”
mentioning
confidence: 99%